2021
DOI: 10.1051/0004-6361/202140441
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional simulations of solar-like models with artificially enhanced luminosity

Abstract: We performed two-dimensional, fully compressible, time-implicit simulations of convection in a solar-like model with the MUSIC code. Our main motivation is to explore the impact of a common tactic adopted in numerical simulations of convection that use realistic stellar conditions. This tactic is to artificially increase the luminosity and to modify the thermal diffusivity of the reference stellar model. This work focuses on the impact of these modifications on convective penetration (or overshooting) at the b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 42 publications
4
31
0
Order By: Relevance
“…Indeed, these modifications can increase the numerical stability of the simulation and accelerate the thermal relaxation. In a first study (Baraffe et al 2021, hereafter Paper I), we performed two-dimensional fully compressible time-implicit simulations of convection in a solarlike model using the MUSIC code. We analysed the impact of increasing the stellar luminosity and thermal diffusivity on convective penetration (or overshooting) at the base of the convective envelope of a solar-like model.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these modifications can increase the numerical stability of the simulation and accelerate the thermal relaxation. In a first study (Baraffe et al 2021, hereafter Paper I), we performed two-dimensional fully compressible time-implicit simulations of convection in a solarlike model using the MUSIC code. We analysed the impact of increasing the stellar luminosity and thermal diffusivity on convective penetration (or overshooting) at the base of the convective envelope of a solar-like model.…”
Section: Introductionmentioning
confidence: 99%
“…Note ho we ver that the convection zone is not precisely adiabatically stratified with super-adiabaticity reaching O (10 −2 ) close to the surface. A close analogue of this initial model has been used in Baraffe et al ( 2021 ) and Le Saux et al ( 2022 ) to study the effects of luminosity boosting. This requires minimizing the super-adiabaticity in the convection zone (so that stratification is not affected by the luminosity boosting).…”
Section: Description Of the Simulationsmentioning
confidence: 99%
“…The relaxation time-scales may be shortened by artificially boosting the stellar luminosity and thermal dif fusi vity. Ho we ver, running such simulations self-consistently requires that the convection zone be adiabatic, to a v oid changes in the temperature stratification due to the boosting (Baraffe et al 2021 ). It has also been shown that boosting can have a significant impact on the dynamics throughout the stellar interior (Baraffe et al 2021 ;Le Saux et al 2022 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, these modifications can increase the numerical stability of the simulation and accelerate the thermal relaxation. In a first study (Baraffe et al 2021, hereafter Paper I), we performed two-dimensional fully compressible time-implicit simulations of convection in a solar-like model using the MUSIC code. We analysed the impact of increasing the stellar luminosity and thermal diffusivity on convective penetration (or overshooting) at the base of the convective envelope of a solar-like model.…”
Section: Introductionmentioning
confidence: 99%